Characterisation of the dip-bump structure observed in proton–proton elastic scattering at √s = 8 TeV - Antchev, G.; Aspell, P.; Atanassov, I.; Avati, V.; Baechler, J.; Baldenegro Barrera, C.; Berardi, V.; Berretti, M.; Borshch, Vladislav; Bossini, E.; Bottigli, U.; Bozzo, M.; et al. (The European physical journal C)
The TOTEM collaboration at the CERN LHC has measured the differential cross-section of elastic proton-proton scattering at root s = 8 TeV in the squared four-momentum transfer range 0.2 GeV2 < vertical bar t vertical bar < 1.9 GeV2. This interval includes the structure with a diffractive minimum (dip) and a secondary maximum (bump) that has also been observed at all other LHC energies, where measurements were made. A detailed characterisation of this structure for root s = 8 TeV yields the positions, vertical bar t vertical bar(dip) = (0.521 +/- 0.007) GeV2 and vertical bar t vertical bar(bump) = (0.695 +/- 0.026) GeV2, as well as the cross-section values, d sigma/dt vertical bar(dip) = (15.1 +/- 2.5) mu b/GeV2 and d sigma/dt vertical bar(bump) = (29.7 +/- 1.8) mu b/Ge-2, for the dip and the bump, respectively.